2017
DOI: 10.3201/eid2311.171145
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Leprosy without Armadillo Exposure, Eastern United States

Abstract: Autochthonous leprosy has been reported in New York City, where there are no wild armadillos. Recent autochthonous cases also have been reported in Georgia and Florida and blamed on armadillos, including cases with no known armadillo exposure. International migration needs to be considered as a cause of autochthonous leprosy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…This data supports that international migration of patients with HD is a likely scenario for human transmission as stated before by Rendini et al [7] The incidence of immigration in Florida was consistently increased between 2010–2014, and about two-thirds of all immigrants to Florida from abroad came from the Americas with a specific increment in those from the Caribbean, and South America [13]. Although notably fewer cases have been recently registered among people migrating from Cuba and Puerto Rico (1.69% of total cases for each country in 2015) [3], immigration from these areas still represents the most likely risk factor for leprosy infection in our Case 3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This data supports that international migration of patients with HD is a likely scenario for human transmission as stated before by Rendini et al [7] The incidence of immigration in Florida was consistently increased between 2010–2014, and about two-thirds of all immigrants to Florida from abroad came from the Americas with a specific increment in those from the Caribbean, and South America [13]. Although notably fewer cases have been recently registered among people migrating from Cuba and Puerto Rico (1.69% of total cases for each country in 2015) [3], immigration from these areas still represents the most likely risk factor for leprosy infection in our Case 3.…”
Section: Discussionsupporting
confidence: 91%
“…After a whole-genome sequencing analysis, Truman et al found that wild armadillos from southern states and U.S. born patients with leprosy are infected with the same strain of M. leprae , demonstrating that zoonotic transmission from nine-banded armadillos is the principal source of infection in this region [5]. Furthermore, Levis et al reported in 2000, the first autochthonous case of leprosy in Toronto, (where there are no wild armadillos) and suggested immigration from endemic countries as the likely scenario for autochthonous transmission of HD [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…About 60%–75% of new cases seen in the USA occur in immigrants, especially those from the Federated States of Micronesia or Marshall Islands, or in people who have close contact with these immigrants 6–8 10. This is thought to be the main form of leprosy transmission in areas such as New York City with high numbers of immigrants and international travellers but no armadillo exposure 11 12. In the last 20 years, the largest number of new leprosy cases has been reported in the Gulf Coast states 4 6 8.…”
Section: Discussionmentioning
confidence: 99%
“…H&E staining shows granulomas as well as epithelioid histiocytes filled with intracellular bacilli 16. The intracellular organisms are acid-fast 11 14. The tissue should also treated with Anti-phenolic glycolipid antigen (PGL)-1 and PCR testing that targets the M. leprae -specific RLEP gene 2 13.…”
Section: Discussionmentioning
confidence: 99%
“…17 Autochthonous leprosy has been reported in metropolitan cities such as New York City, thought to be related to international migration. 18 A leprosy clinic at Emory reported managing 37 patients referred from 2002 to 2014. 19 There are also rare cases reported in other developed countries, including Canada and European nations, generally related to foreign travel.…”
mentioning
confidence: 99%